Tail Nerve Electrical Stimulation and Electro-Acupuncture Can Protect Spinal Motor Neurons and Alleviate Muscle Atrophy after Spinal Cord Transection in Rats. (28th June 2017) - Zhang, Yu-Ting; Jin, Hui; Wang, Jun-Hua; Wen, Lan-Yu; Yang, Yang; Ruan, Jing-Wen; Zhang, Shu-Xin; Ling, Eng-Ang; Ding, Ying; Zeng, Yuan-Shan
Abstract : Spinal cord injury (SCI) often results in death of spinal neurons and atrophy of muscles which they govern. Thus, following SCI, reorganizing the lumbar spinal sensorimotor pathways is crucial to alleviate muscle atrophy. Tail nerve electrical stimulation (TANES) has been shown to activate the central pattern generator (CPG) and improve the locomotion recovery of spinal contused rats. Electroacupuncture (EA) is a traditional Chinese medical practice which has been proven to have a neural protective effect. Here, we examined the effects of TANES and EA on lumbar motor neurons and hindlimb muscle in spinal transected rats, respectively. From the third day postsurgery, rats in the TANES group were treated 5 times a week and those in the EA group were treated once every other day. Four weeks later, both TANES and EA showed a significant impact in promoting survival of lumbar motor neurons and expression of choline acetyltransferase (ChAT) and ameliorating atrophy of hindlimb muscle after SCI. Meanwhile, the expression of neurotrophin-3 (NT-3) in the same spinal cord segment was significantly increased. These findings suggest that TANES and EA can augment the expression of NT-3 in the lumbar spinal cord that appears to protect the motor neurons as well as alleviate muscle atrophy.